Sustainable tourism development - Amerta, I Made Suniastha; Sara, I Made; Bagiada, Kompiang (International Research Journal of Management, IT & Social Sciences, 2018)
As a global phenomenon, tourism sector plays a very significant role in the global economic development for the last three decades. This sector has given a very fundamental endorsement of income to many countries all over the world. This article tries to explain the concepts of sustainable development in the tourism sector which were taken from some sources and how tourism as an essential industry can be developed sustainably. It is expected that the development of sustainable tourism should be able to handle the three basic principles of ecological sustainability, social and cultural sustainability, and economic sustainability for both present and future generations. In other words, sustainable tourism development should always beneficial and give a good effect to the local communities, governments, and investors as tourism stakeholders at present days as well as in the future time.